Det vingede ord - Hauge, Hans (Grundtvig-Studier, 1992)
The pithy saying Peter Baslev-Clausen: THe pithy saying: About N.F.S. Grundtvigs writing of hymns. (Materialecentralen, Copenhagen 1991) 143 sites. Reviewed by Hans Hauge